Design and Manufacture of 3 Phase Electric Engine Hydrophore Control System - Hasiah Hasiah (Ridwan Institute, 2023)
On board there is a temporary water reservoir called a hydrophore? Hydrophore serves to distribute fresh water that will flow to all parts of the ship's hull or accommodation on the ship, the hydrophore pressure tank cannot work for a long time if the ship is in black out condition. This research method is a type of Experimental research. Data collection techniques carried out are observation, design, making, measurement and documentation. The analysis method uses a descriptive analysis method by describing the working principle of the 3 Phase Electric Machine Hydrophore Control System that has been designed and made by the Research Team. The results of the study produced a 3 Phase Electric Machine Hydrophore Control System trainer we made with the hope that it can be a material or learning tool for students studying at the Polytechnic of Shipping Sciences, especially cadets / cadets of Diploma IV Shipping students who have not carried out sea practice so that when they carry out sea practice there is already an idea they get about the Hydrophore control system Although the tool we made is only a miniature because the tank we use is on a small size scale.